The Politics of the Internet in Third World Development: Challenges in Contrasting Regimes with Case Studies of Costa Rica and Cuba - Hoffmann, Bert (Latin American Studies, 2004)
This book examines the political and developmental implications of the new information and communication technologies (NICT) in the Third World. Whereas the concept of the "digital divide" tends to focus on technological and quantitative indicators, this work stresses the crucial role played by the political regime type, the pursued development model and the specific configuration of actors and decision-making dynamics. Two starkly contrasting Third World countries, state-socialist Cuba and the Latin America's "show-case democracy" Costa Rica, were chosen for two in-depth empirical country studies. Bert Hoffmann is Senior Research Fellow at the GIGA Institute of Latin American Studies. Introduction Part I: Third World Development and NICT in Political Perspective 1. The New Information and Communication Technologies (NICT): Comparative Experiences and Present Disparities 2. NICT in Third World Development: Political Issues in a Transformed Telecommunications Regime Part II: Latin America's 'Mixed Model': Costa Rica 3. The Costa Rican Development Model and Its Telecommunications Regime 4. Active NICT Development by State Monopoly: A New Costa Rican Model? Part III: Latin America's 'Socialist Model': Cuba 5. Cuba's State-Socialist Development Model and Its Telecommunications Regime 6. From the Rejection of the Internet to the 'Informatization of Society': A Political Anatomy of Change 7. The Politics of the Internet in Third World Development: Conclusions in Comparative Perspective